Rights, religious pluralism and the recognition of difference : off the scales of justice - Gozdecka, Dorota Anna (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2016)
'Human rights and inclusion are the leading legal paradigms of our time and are considered to be the cornerstone of democracy. In legal discourses on rights, freedom of religion occupies a pivotal position, receiving increasing attention from legal bodies. This book critically evaluates the emerging legal principles and standards that are applied to religious freedom in Europe. Focusing on religious pluralism as an interpretational principle stemming from attempts to define the boundaries of freedom of religion, it examines the expansion of religious pluralism as an underlying principle of different rights regimes and constitutional traditions. It is, however, the static and liberal shape this principle has assumed that is taken up critically here: in order to address how difference is vulnerable to elimination rather than recognition; and through the lens of a contemporary ethics of alterity to reconstruct the possibility of a true religious pluralism'
'Human rights and inclusion are the leading legal paradigms of our time and are considered to be the cornerstone of democracy. In legal discourses on rights, freedom of religion occupies a pivotal position, receiving increasing attention from legal bodies. This book critically evaluates the emerging legal principles and standards that are applied to religious freedom in Europe. Focusing on religious pluralism as an interpretational principle stemming from attempts to define the boundaries of freedom of religion, it examines the expansion of religious pluralism as an underlying principle of different rights regimes and constitutional traditions. It is, however, the static and liberal shape this principle has assumed that is taken up critically here: in order to address how difference is vulnerable to elimination rather than recognition; and through the lens of a contemporary ethics of alterity to reconstruct the possibility of a true religious pluralism'
Introduction -- Council of Europe bodies and soft-law interpretations of religious pluralism -- The European Court of Human Rights and judicial interpretation of the principle of religious pluralism -- Relevance of religious pluralism in the EU legal order -- Relevance of pluralism in European domestic regimes -- On the way to Elysium : defining religion and registration of new religious communities -- Regulation of religious symbols : a European Pandora's jar -- Religions and reproductive rights : freedom changed to stone? -- The hollow paradigms of contemporary debates on law and religion and the failed potential of religious pluralism -- Repairing the utopia of rights : sources of reconstruction -- Human rights and the dissident -- Rights beyond structure? Towards otherwise than becoming -- Conclusions.
Includes bibliographical references and index.
Keywords: Freedom of religion -- Europe; Civil rights -- Europe; Religious pluralism -- Europe; LAW / General; LAW / Conflict of Laws; LAW / Discrimination